A Practical Spanish Grammar for Border Patrol Officers - Immigration and Naturalization Service (Department of Justice), Washington, DC.; Immigration and Naturalization Service (Department of Justice), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
Written for probationary patrol inspectors at the Border Patrol Training School, El Paso, Texas, this text presents a concise, traditional analysis of Spanish grammar. Each of the 21 lessons focuses on an aspect of the language including sections on the parts of speech, special verbs, commands, numbers, passive voice, and the subjunctive mood. A unit on comparative word study is included. The appendix contains numerous translation of textual dialogues, verbs, practice materials, useful expressions, and vocabulary lists. The expressions and dialogues used in the text reflect the culture of the Spanish-speaking population along the border and the type of activities with which the border patrol officer is often concerned. For the earlier edition see ED 028 675. (RL)
Availability: Superintendent of Documents, U. S. Government Printing Office, Washington, D.C. 20402 (GPO-0-403-4600, $1.25).
ERIC Note: Revised 1970.
Educational level discussed: Adult Education.
Microfiche.
Keywords: Adult Education; Conventional Instruction; Cultural Education; Form Classes (Languages); Grammar; Language Instruction; Mexican Americans; Modern Languages; Morphology (Languages); Sentence Structure; Spanish; Spanish Speaking; Traditional Grammar; Verbs; Vocabulary